Monoclonal antibody production: viability improvement of RC1 hybridoma cell in different types of bioreactor - Mel, Maizirwan; Abdul Rahman, Abdul Rafiz; Hasim, Yumi Hasyun; Ali, Abdul Manaf (2005)
A study was done to determine the viability improvement of hybridoma cell producing monoclonal antibody. Using the optimized media, the RC1 hybridoma cells were cultured in T-Flask, MiniPerm bioreactor, and stirred tank bioreactor. The study show that the performance of hybridoma cells growth in the three different culture systems has revealed that in stirred tank bioreactor gave the highest cell percentage of viability (> 90% for five days) and the highest specific growth rate. The growth kinetic values for specific growth rate (μ) obtained from T-Flask, MiniPerm and stirred bioreactor were 0.0151, 0.0243 and 0.0289h-1, respectively. While, the values of doubling time (td) obtained from T-Flask, MiniPerm and stirred bioreactor were 46, 29, and 24h, respectively.